Effect of Unripe Plantain (Musa paradisiaca) and Ginger (Zingiber officinale) on Renal Dysfunction in Streptozotocin-Induced Diabetic Rats - Iroaganachi, Mercy; Eleazu, Chinedum; Okafor, Polycarp (JOP. Journal of the Pancreas, 2015)
Context Although unripe plantain (Musa paradisiaca) and ginger (Zingiber officinale) are used as single plants to manage diabetes mellitus in Nigeria, the possibility of combining them in a typical diabetic diet and the glycemic response elicited as a result of such combination has not been investigated. Objective To determine the effect of unripe plantain and ginger on serum total proteins, albumin, creatinine and urea levels of streptozotocin induced diabetic rats. Methods Twenty four male albino rats were used and were divided into 4 groups of 6 rats each. Group 1 (non-diabetic) received standard rat feeds; Group 2 (diabetic) received standard rat feeds; Group 3 received unripe plantain pellets and Group 4 received unripe plantain+ginger pellets. Results There were significant increases (P=0.045) of both serum urea and creatinine, but significant decreases (P=0.045) of both serum total protein and albumin levels, in Group 2 rats compared with Group 1. There were significant decreases (P=0.033) of both serum urea and creatinine levels of Group 3 and 4 rats compared with Group 2. In addition, there were significant increases of both serum total protein and albumin levels (P=0.033) in Group 3 rats compared with Group 2, but the comparison of serum total protein and albumin levels between Group 4 and Group 2 did not reach the significant level (P=0.056 and P=0.065 for serum total protein and albumin levels, respectively. Conclusion Combination of unripe plantain and ginger at the ratio used in the management of renal dysfunction in diabetics was not very effective compared with unripe plantain alone. Image: Serum albumin levels of diabetic rats.